2020
DOI: 10.5194/acp-20-771-2020
|View full text |Cite
|
Sign up to set email alerts
|

Natural sea-salt emissions moderate the climate forcing of anthropogenic nitrate

Abstract: Abstract. Natural sea-salt aerosols, when interacting with anthropogenic emissions, can enhance the formation of particulate nitrate. This enhancement has been suggested to increase the direct radiative forcing of nitrate, called the “mass-enhancement effect”. Through a size-resolved dynamic mass transfer modeling approach, we show that interactions with sea salt shift the nitrate from sub- to super-micron-sized particles (“redistribution effect”), and hence this lowers its efficiency for light extinction and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 70 publications
(106 reference statements)
0
15
0
Order By: Relevance
“… 28 , 29 It is desirable to improve the parametrization of γ for a better understanding of nitrate formation and its environmental impact. 30 , 31 …”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 , 29 It is desirable to improve the parametrization of γ for a better understanding of nitrate formation and its environmental impact. 30 , 31 …”
Section: Recent Developmentsmentioning
confidence: 99%
“…For example, reactive uptake coefficients (γ) for N 2 O 5 on atmospheric aerosols varied over a wide range of 10 –5 to 10 –1 and were more strongly correlated with aerosol water content than with other parameters . Zheng et al had to adopt high uptake coefficients close to 0.1 (similar to mineral dust) to reproduce the observed nitrate concentrations during severe haze in Beijing, while observation-based closure studies revealed uptake coefficients from 0.009 to 0.072 in Beijing and southern China. , It is desirable to improve the parametrization of γ for a better understanding of nitrate formation and its environmental impact. , …”
Section: Recent Developmentsmentioning
confidence: 99%
“…ozone production (Vinken et al, 2014;Visser et al, 2019;Mertens et al, 2020a) as well as on heterogeneous processes, e.g. par-V. Kumar et al: Regional model evaluation using MAX-DOAS ticulate nitrate production (Chen et al, 2020). Various studies have shown that significant improvements in satellite retrievals can be achieved through the incorporation of highly resolved a priori trace gas and aerosol fields calculated by high-resolution regional models (Valin et al, 2011;Liu et al, 2020;Ialongo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, will strengthen the nitrate's climate cooling feedback [7][8][9][10], called "mass-enhancement effect" [10]. Coarse particle dominance of SS will shift the total mass of nitrate from sub-to super-micron (coarse) sizes, called the "redistribution effect", counteracting the mass-enhancement effect [10]. In other cases, super-micron SS may also effectively mix with anthropogenic sulphate aerosols originating from continental emissions of sulfur dioxide, causing a reduction in the extinction efficiency of sulphate [11].…”
Section: Introductionmentioning
confidence: 97%
“…Water-soluble cations originating from SS such as potassium, sodium, magnesium, and calcium react with nitrate, elevating its total column loading through the uptake of nitric acid [6]. This, in turn, will strengthen the nitrate's climate cooling feedback [7][8][9][10], called "mass-enhancement effect" [10]. Coarse particle dominance of SS will shift the total mass of nitrate from sub-to super-micron (coarse) sizes, called the "redistribution effect", counteracting the mass-enhancement effect [10].…”
Section: Introductionmentioning
confidence: 99%